How does collective practice function as an artistic strategy - Weber, Deborah (Michaelis School of Fine Art, 2020)
This research interrogates the different strategies and methodologies employed by collectives (with a focus on South African collectives in the past two decades) to raise fundamental questions about art; the nature of artistic work, forms of production, authorship, autonomy and collaboration as an artistic strategy. The research sets out to explore collaboration as a field of art practice. The criteria for selection of the collectives in the research was each collective needed to comprise of three or more artists who have produced and authored work together under an umbrella name, they also needed to use multi-disciplinary practices. The selection included: Galerie Puta (2003), Avant Car Guard (2004), Doing it for Daddy (2006), Gugulective (2006), Centre for Historical Enactments (2010), Burning Museum (2013) and iQhiya (2015), Guerilla Girls (1985), Laboratoire Agit’Art (1975), Raqs Media Collective (1992), Ubulungiswa/Justice and Karoo Disclosure (2014). The idea of shared authorship is the central tenet around which all collective practice revolves. This thesis looks at the collective authorial voice as a strategic artistic practice in contemporary art that enables reappraisals of artistic production. Furthermore it interrogates the decentralization of authorship, as an artistic strategy to shift paradigms of thinking in relation to power structures, be it institutional, political or ideological.